2015
DOI: 10.1002/pmic.201400493
|View full text |Cite
|
Sign up to set email alerts
|

The interactions between mitochondria and sarcoplasmic reticulum and the proteome characterization of mitochondrion‐associated membrane from rabbit skeletal muscle

Abstract: To obtain a comprehensive understanding of proteins involved in mitochondrion-sarcoplasmic reticulum (SR) linking, a catalog of proteins from mitochondrion-associated membrane (MAM) of New Zealand white rabbit skeletal muscle were analyzed by an optimized shotgun proteomic method. The membrane fractions were prepared by differential centrifugation and separated by 1D electrophoresis followed by a highly reproducible, automated LC-MS/MS on the hybrid linear ion trap (LTQ)-Orbitrap mass spectrometer. By integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…In support of this, SYNJ2BP, which we identified in our study, has not previously been enriched in any MS-based MAM proteomic study (Horner et al, 2015; Liu et al, 2015; Poston et al, 2013; Zhang et al, 2011). Indeed, the majority of functions thus far attributed to mitochondria-ER contact sites—e.g.…”
Section: Discussionsupporting
confidence: 83%
“…In support of this, SYNJ2BP, which we identified in our study, has not previously been enriched in any MS-based MAM proteomic study (Horner et al, 2015; Liu et al, 2015; Poston et al, 2013; Zhang et al, 2011). Indeed, the majority of functions thus far attributed to mitochondria-ER contact sites—e.g.…”
Section: Discussionsupporting
confidence: 83%
“…Superresolution microscopy of overexpressed VDACs indicated that VDAC1 and 2 form clusters, whereas VDAC3 distributes more homogenously [41]. A site of special interest in the distribution of VDAC2 is the OMM domain that is coupled to the sarco/endoplasmic reticulum (SR/ER) membrane, the mitochondria associated membrane (MAM) where the presence or enrichment of all VDAC isoforms has also been shown [42,43]. …”
Section: Gene Expression Protein Abundance and Distributionmentioning
confidence: 99%
“…MAMs purification yields the ensemble of membranes that are bound to the ER, including the lipid-MERCs, the ion-MERCs, the phago-MERCs, the ribo-MERCs and the sites where ER tubules contact mitochondria to mediate the Drp-1-dependent constriction that guides mitochondria division, 81,82 the fission-MERC. As such, the current MAM proteomes, 83,84 are representative of the protein collections of all types of MERCs in the tissue and cell type from which the MAMs were isolated. Similarly, localization of major protein complexes like the γ-secretase 30,57 and mTORC2 85 at the MAMs will need to be investigated by immunogold analysis, to associate their localization to a specific MERC thickness and, therefore, function.…”
Section: 80mentioning
confidence: 99%